2021
DOI: 10.7759/cureus.17938
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Associated With TNF Alpha Inhibitor Use in Patients With Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by inflammation and pannus formation, with subsequent joint and cartilage degradation. Treatment commonly targets inflammatory cytokines, including tumor necrosis factor (TNF) alpha, which is a potent inflammatory cytokine required for cell signaling, regulation, and apoptosis, as well as for other cellular functions including immune response. TNF alpha inhibitors have demonstrated benefits in improving RA patient outcomes in terms of immune func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(51 reference statements)
0
6
0
4
Order By: Relevance
“…That is why they have been involved in deteriorating patients with heart failure. 95 However, other studies have shown that anti-TNF therapy reduces subclinical myocardial inflammation and improves cardiovascular function in patients with rheumatic diseases, including RA. 96 Additionally, it has been demonstrated that TNF-α blocking agents may be related to reduced risk of cardiovascular events compared to non-biological DMARDs.…”
Section: Medicines Commonly Used In Rheumatoid Arthritis and Their Im...mentioning
confidence: 99%
“…That is why they have been involved in deteriorating patients with heart failure. 95 However, other studies have shown that anti-TNF therapy reduces subclinical myocardial inflammation and improves cardiovascular function in patients with rheumatic diseases, including RA. 96 Additionally, it has been demonstrated that TNF-α blocking agents may be related to reduced risk of cardiovascular events compared to non-biological DMARDs.…”
Section: Medicines Commonly Used In Rheumatoid Arthritis and Their Im...mentioning
confidence: 99%
“…TNF- α plays an important role in this pathological process [ 98 ]. Patients with RA are systemically predisposed to high levels of TNF- α [ 99 ]. It is generally accepted that RA and atherosclerosis are autoinflammatory diseases involving multiple inflammatory cytokines, with many common genetic predispositions and environmental factors [ 100 ].…”
Section: Tnf- α Antagonist and Chd In Patients Wit...mentioning
confidence: 99%
“…Cardioprotective effects of TNF- α antagonists may be related to the inhibition of TNFR1 [ 123 ]. However, inhibition of TNFR2, a cardioprotective receptor, by TNF- α antagonists exceeds that of TNFR1, resulting in increased cardiovascular morbidity [ 99 ]. The contrast in the risk of CVD can be explained by the difference in doses administered, causing different degrees of inhibition in TNFR2.…”
Section: Tnf- α Antagonist and Chd In Patients Wit...mentioning
confidence: 99%
“…Как известно, фактор некроза опухоли альфа (TNFα), доминирующий медиатор воспаления в патогенезе РА, способствует прогрессированию симптомов РА и является внешним фактором, осуществляющим запуск рецепторного варианта апоптоза через семейство TNF-рецепторов. Специализированные рецепторы из семейства TNF для индукции апоптоза -CD95 (Fas/Apo-l), TNF-R1, TRAIL-Rl, TRAIL-R2Hflp, DR3, DR6, EDA-R и NGF-R, находятся на цитоплазматической мембране клеток [16]. Апоптоз, опосредованный рецептором CD95, Fas и другими членами данного семейства, образует мультибелковый комплекс, необходимый для взаимодействия с обязательными для индукции апоптоза адапторными молекулами, в том числе с доменом цитозольного проэнзима прокаспазы 8.…”
Section: Introductionunclassified
“…Помимо инициации апоптоза, лигирование рецепторов смерти также может вызывать некроптоз, при котором не происходит фрагментация ДНК, а гибель клетки по механизму некроптоза вызывает мощный иммунный ответ, в том числе и пролиферацию. Внешние пути апоптоза и некроптоза регулируют друг друга [16]. В другом исследовании характеризуют каспазу 8 как молекулярный переключатель, контролирующий апоптоз, некроптоз и пироптоз и предотвращающий повреждение тканей во время эмбрионального развития и взросления [12].…”
Section: Introductionunclassified